(untitled) (Bangladesh Rice Journal, 2025)
The research aimed to evaluate the effects of hormones and callus age on in vitro regeneration as well as seeking to establish a reliable and effective plant regeneration protocol for the rice varieties BRRI dhan92 and BRRI dhan96. Mature seeds were used to initiate callus induction using MS media containing 2 mg/L of 2,4-D. For the regeneration process, calli were transferred to MS medium supplemented with different hormone combinations: H1 (2 mg/L BAP + 1 mg/L NAA + 1 mg/L Kinetin), H2 (4 mg/L BAP + 0.5 mg/L NAA + 1.2 mg/L Kinetin), and H3 (1 mg/L BAP + 1 mg/L NAA + 1 mg/L Kinetin). Significant variations were observed in the response to plant hormones between the rice varieties. Additionally, calli of ten, fifteen, and twenty-one days old were tested to observe the effect of callus age on plant regeneration. The highest callus induction frequency was recorded in BRRI dhan92 (88.17%). The H2 hormone combination showed the highest regeneration frequencies, achieving 63.67% in BRRI dhan92 and 45.33% in BRRI dhan96. Furthermore, the highest regeneration frequencies were found in ten-day-old calli, with BRRI dhan92 at 67.00% and BRRI dhan96 at 49.00%. This optimized regeneration protocol for BRRI dhan92 and BRRI dhan96 can be effectively used for Agrobacterium-mediated genetic transformation and their subsequent improvement. Bangladesh Rice J. 27(2): 17-24, 2023